Are mild cleansers appropriate for hand hygiene in the COVID era? An in vitro investigation of the antiviral efficacy of different hand hygiene products - Winder, Natalie; Ashraf, Zahra; Gohar, Sara; Baalbaki, Nada; Cork, Micheal; Danby, Simon; Muthana, Munitta (Frontiers in Virology, 2023)
Background Washing hands with soap and lukewarm water for 20 s is a fundamental measure advocated especially within the UK to help control the spread of viral disease. However, these practices can induce irritant contact dermatitis, particularly in healthcare professionals (HCPs). HCPs typically manage their condition by replacing soap or alcohol-based hand sanitizers with cleansers containing mild surfactants and/or emollient ingredients [skin-friendly cleansers (SFCs)] to mitigate skin damage and/or using topical emollients after washing for repair. Despite this widespread practice, there is very limited evidence supporting the efficacy of these interventions in the prevention of viral propagation. Methodology Within this study a range of viruses comprising human coronavirus (HCoV), herpes simplex virus (HSV)-1, influenza (IVA), adenovirus (Ad), and murine norovirus (MNV) were tested against multiple hand wash products, including SFCs. In vitro analysis using plaque assays and tissue culture infectious dose 50 (TCID50) were used to assess virus infectability after incubation with the test products (soaps and SFCs) over a range of concentrations and time points. Transmission electron microscopy (TEM) was used to determine virus architecture and size, while viral replication genes were measured by reverse transcription-polymerase chain reaction (RT-PCR). Results/conclusions Enveloped viruses demonstrated greater susceptibility over a range of test products, suggesting some SFCs are a suitable alternative to soap (depending on the presence of a viral envelope). However, no virucidal activity was observed for non-enveloped viruses. Water type (i.e., soft/hard) and pre-exposed hand hygiene conditions (i.e., clean/dirty) made little difference to the effectiveness of both soaps and SFCs. Therefore, new hand hygiene regimens should be implemented based on trying to encompass all viruses with varying structures, with specific emphasis on the absence of a viral envelope.